Aroma Components in Freon Extracts of Wine - Augustyn, 0.P.H.; Marais, J. (South African Journal of Enology and Viticulture, 2017)
The utility of a standard analysis technique for wine volatiles was expanded by the identification of eleven new components in the standard chromatogram. Acetoin was identified as the component interfering with the determination of hexyl acetate, whilst ethyl 3-hydroxybutyrate was positively identified as a constituent of Cabernet Sauvignon wine aroma.